2021
DOI: 10.1021/acsami.1c00829
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Protonation of Tailor-Made Polypiperazines and Endosomal Escape for Cytosolic Protein Delivery

Abstract: Responsive polymers, which become protonated at decreasing pH, are considered a milestone in the development of synthetic cell entry vectors. Exact correlations between their properties and their ability to escape the endosome, however, often remain elusive due to hydrophobic interactions or limitations in the design of water-soluble materials with suitable basicity. Here, we present a series of well-defined, hydrophilic polypiperazines, where systematic variation of the amino moiety facilitates an unprecedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…[168,178,179] Primarily, live cell microscopy is used, also allowing kinetic studies. [172,183] Less commonly, cells are studied after fixation. [178,190] Fixation with subsequent permeabilization may complicate the interpretation of the calcein assay due to false positive results as a result of fixation artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…[168,178,179] Primarily, live cell microscopy is used, also allowing kinetic studies. [172,183] Less commonly, cells are studied after fixation. [178,190] Fixation with subsequent permeabilization may complicate the interpretation of the calcein assay due to false positive results as a result of fixation artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…However, this value is lower than that of polymers presenting a tertiary amine function, such as poly(2-(dimethyl amino)ethyl methacrylate PDMAEMA (pK a = 7.5) [22] and could be due to the steric hindrance of the heterocycle which renders the tertiary amine less accessible to protonation by the acid [23]. Hausig et al [13] reported low pK a values (between 6 and 7.1) for polymers comporting N-alkyl-piperazine units. Low pK a values were also observed for poly(2-methyl-acrylic acid 2-[(2-(dimethylamino)-ethyl)-methylamino]-ethyl ester), [24] a polymer used in cellular transfection.…”
Section: Acido-basic Properties Of Thoxma and Pthoxmamentioning
confidence: 96%
“…Changes in this physiological pH are often symptomatic of the presence of infections or cancer [12]. Morpholine-derived polymers contain tertiary amino groups which are protonated in acidic pH (pK a of morpholine = 8.3) [13,14]. This property can be used to tailor the behaviour of the polymer in different biological environments [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations